Antiphospholipid Sundrome in Childhood Systemic Lupus Erythematosus - Paudyal, B (Journal of Nepal Health Research Council, 2010)
Antiphospholipid syndrome is an autoimmune disease that presents with recurrent arteriovenous thrombosis, repeated pregnancy loss and elevated titres of anti phospholipid antibodies in the blood. It is a common cause of acquired thrombosis and can manifest within any part of the vascular tree. Inferior Venacava thrombosis at outset, however, is not a common manifestation of systemic lupus erythematosus associated- antiphospholipid syndrome particularly in children. Here, we present a 14-year old girl who developed antiphospholipid syndrome as a presenting manifestation of systemic lupus erythematosus. Â Key words: antiphospholipid syndrome, thrombosis, systemic lupus erythematosus